2020
DOI: 10.1007/s11104-020-04584-3
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs among phosphorus-acquisition root traits of crop species for agroecological intensification

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 59 publications
0
38
0
2
Order By: Relevance
“…Cover crops influence P-cycling within soil-plant systems (Eichler-Löbermann et al 2009;Honvault et al 2020). In this study, combined chemical, biochemical, and microbiological methods were used to elucidate whether the growth of cover crops in combination with no-till might change microbial abundance and functions and lead to modifications in plant available P pools in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Cover crops influence P-cycling within soil-plant systems (Eichler-Löbermann et al 2009;Honvault et al 2020). In this study, combined chemical, biochemical, and microbiological methods were used to elucidate whether the growth of cover crops in combination with no-till might change microbial abundance and functions and lead to modifications in plant available P pools in soil.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other mechanisms to access the high molecular weight organic N may differ between the species. As plant species differ in their preferences to N and P forms, analogically their strategies of N and P acquisition also differ [54,[66][67][68].…”
Section: Plant Physiology-specificmentioning
confidence: 99%
“…Therefore, rational P fertilisation should be considered for efficient Zn biofortification on Zn-deficient soils and phytoremediation of Zncontaminated soils. Honvault et al (2021) found that plant P-acquisition strategies are driven by multiple belowground morphological and physiological traits as well as interactions among these traits. Interactions and trade-offs among belowground functional traits, however, remain underexplored, especially for fast-growing crops such as cover crops, limiting our understanding of P cycling in agroecosystems.…”
Section: Soil-plant Interactions Are Important For Climate Change Mitigationmentioning
confidence: 99%